The psychology of preaching: the power of diaries - Fontaine, Rodrigue Ancelot Harvey (ISTAC, 2015)
Recent discoveries in neuroscience shows that individuals have an impulsive system and a reflective system. These two systems are protected by powerful psychological defense mechanisms. In particular, confirmation bias, cognitive and the way people remember and forget information can prevent learning new things about Islam. To be effective, Muslim preachers must overcome these defense mechanisms so that new knowledge about Islam can be internalised. To achieve this goal, this author experimented with students at the International Islamic University Malaysia. Since 2010, over 1,100 students have listened to Islamic videos on a weekly basis throughout the semester and kept a diary documenting their reflections. Both qualitative and quantitative data are presented. The analysis suggest that keeping diary is a useful way to overcome defense mechanisms. This author conclude that preachers can think about shifting their role from providing content about Islam to providing a process for helping Muslims discover new things about Islam.